MICROPROPAGATION OF OROXYLUM INDICUM (L.) KURZ - Phu Hiep Hoang; Thi Hong Tran (Tạp chí Khoa học Đại học Đà Lạt)
This study develops a basic micropropagation protocol for Oroxylum indicum, a well-liked plant in Southeast Asia with medicinal properties that have been recognized by various civilizations worldwide for centuries. Seeds were sterilized with 0.1% HgCl2 for 1 minute, yielding an optimal sterilization efficiency of 89.9%. MS medium supplemented with 1.0 mg/l BAP was the most effective medium for shoot initiation, and MS medium supplemented with 0.7 mg/l IBA was the best rooting medium.